(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The present study was conducted to prepare Fish peptide powder (FPP) through enzymatic hydrolysis of low-cost fish, white croaker (Otolithoides pama) and to determine its nutritional and functional properties. As source of extracellular protease, three types of enzymes viz. purified papain, papaya peel and ginger were used in triplicates and these enzymes were found to be very effective to break the fish muscle protein down. Highest protein concentration (89.12%) was found in peptides using purified papain followed by using papaya peel (87.46%) and ginger (76.04%). Solubility, foam expansion and emulsifying activity index (EAI) were determined to analyze its functional properties. Purified papain showed the highest solubility (84%) followed by 80% and 72% in FPP using papaya peel and ginger respectively. Three sample concentrations (0.1%, 0.5% and 1%) were used in triplicates to determine foam expansion percentage and EAI. The stability of foam was increased and EAI was decreased with increasing concentrations of samples. The study concluded that papaya peel would be a source of low-cost protease enzyme as an alternative of purified papain as the protein percentage did not vary significantly. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (3), 214-218